2017
DOI: 10.3390/molecules22122242
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Multicomponent Traditional Herbal Medicine by HPLC–MS and Electron and Light Microscopy

Abstract: Background: Commercial pharmaceutical herbal products have enabled people to take traditional Chinese medicine (TCM) in a convenient and accessible form. However, the quantity and quality should be additionally inspected. To address the issue, a combination of chemical and physical inspection methods were developed to evaluate the amount of an herbal formula, Xiang-Sha-Liu-Jun-Zi-Tang (XSLJZT), in clinical TCM practice. Methods: A high-performance liquid chromatography–tandem mass spectrometry (HPLC–MS) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…As reviewed by Leier et al biotechnology-based therapeutic strategies, such as cDNA replacement, CRISPR-based DNA repair and exon skipping, are being developed as a form of mutation-directed therapies to repair the NF1 gene [ 71 ]. Furthermore, since the loss of NF1 in glial cells has been found to be associated with increased RAS activity, targeting the RAS-downstream signaling pathways (e.g., the RAF-MEK-ERK signaling cascade) through MEK inhibition may be another viable therapeutic strategy to prevent NF1-associated mesenchymal transformation in GBM [ 17 , 57 , 78 ].…”
Section: The Transcriptome Of Mesenchymal Glioblastomamentioning
confidence: 99%
“…As reviewed by Leier et al biotechnology-based therapeutic strategies, such as cDNA replacement, CRISPR-based DNA repair and exon skipping, are being developed as a form of mutation-directed therapies to repair the NF1 gene [ 71 ]. Furthermore, since the loss of NF1 in glial cells has been found to be associated with increased RAS activity, targeting the RAS-downstream signaling pathways (e.g., the RAF-MEK-ERK signaling cascade) through MEK inhibition may be another viable therapeutic strategy to prevent NF1-associated mesenchymal transformation in GBM [ 17 , 57 , 78 ].…”
Section: The Transcriptome Of Mesenchymal Glioblastomamentioning
confidence: 99%
“…XSLJZT is a herbal formula that contains a high polyphenol content. Liu et al reported that glycyrrhizin and liquiritin from Glycyrrhiza uralensis ( Gan Cao ), quercetrin, and hesperidin from Citrus reticulata ( Chen Pi ), ginsenoside Rg1, ginsenoside Re, ginsenoside Rb1 from Panax ginseng ( Ren Shen ), 6-gingerol and 6-shogaol from Zingiber officinale , and costunolide and dehydrocostus lactone from Aucklandia lappa ( Mu Xiang ) could be detected in XSLJZT using HPLC-MS ( Liu et al, 2017 ). Polyphenols can potentially influence the cytotoxicity of chemotherapeutic drugs either by additive or synergistic effects, which can result in toxicity ( Mahbub et al, 2015 ; Klimaszewska-Wisniewska et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2 g), Sha ren), and Aucklandiae Radix ( Aucklandia costus Falc. (2 g), Mu xiang) ( Liu et al, 2017 ). All materials were purchased from Sun Ten Pharmaceutical (New Taipei City, Taiwan) and authenticated by a non-profit organization, Brion Research Institute of Taiwan (New Taipei City, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological and microscopic identifications were the most accepted conventional methods (Xu, Song, Zhou, Li, & Li, 2015), of which the former was suitable for intact raw herbs, and the latter was appropriate for the herbs that were broken or powdered (Zafar, Ahmad, Sultana, & Lubna, 2019; Zhao, Liang, & Ping, 2011). And as for some medicinal herbs that have been made into some dosage forms such as decoction, granules or tinctures, chemical profiling was preferred (Liu, Cheng, Hsieh, & Tsai, 2017). Nevertheless, there were few studies on the comparison of chemical constituents between VTF and its adulterants.…”
Section: Introductionmentioning
confidence: 99%